The language and literature of the New Testament : essays in honour of Stanley E. Porter's 60th birthday - Porter, Stanley E., 1956-; Fuller Dow, Lois K. (Biblical Interpretation Series, 2016)
In The Language and Literature of the New Testament , a team of international scholars assembles to honour the academic career of New Testament scholar Stanley E. Porter. Over the years Porter has distinguished himself in a wide range of sub-disciplines within New Testament Studies. The contents of this book represent these diverse scholarly interests, ranging from canon and textual criticism to linguistics, other interpretive methodologies, Jesus and the Gospels, and Pauline studies.